2020
DOI: 10.1017/exp.2020.29
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of a brief mindfulness induction on motor inhibitory control

Abstract: Inhibitory control can be divided into motor and cognitive inhibition. The current research is the first study exploring the impact of brief mindfulness training on motor inhibition, measured by a stop signal task in participants without any meditation experience. Motor inhibition performance was compared before and immediately after three different conditions; a brief mindfulness induction, a resting state and an active control session in which participants listened to their favorite music. Post-test learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…For perceptual inhibition, some studies reported benefits [e.g., ( Luu and Hall, 2017 )] while others reported no effects [e.g., ( Polak, 2009 )]. Regarding motor inhibition, which has been scarcely investigated, studies reported short-term MM effects at the neural level ( Andreu et al, 2018 ), but not at the behavioral level ( Andreu et al, 2018 ; Jaiswal et al, 2020 ; Baranski, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For perceptual inhibition, some studies reported benefits [e.g., ( Luu and Hall, 2017 )] while others reported no effects [e.g., ( Polak, 2009 )]. Regarding motor inhibition, which has been scarcely investigated, studies reported short-term MM effects at the neural level ( Andreu et al, 2018 ), but not at the behavioral level ( Andreu et al, 2018 ; Jaiswal et al, 2020 ; Baranski, 2021 ).…”
Section: Discussionmentioning
confidence: 99%